PEMANFAATAN POJOK BACA DALAM MENINGKATKAN MINAT MEMBACA SISWA KELAS III SDN 14 TRANS SABUNG TAHUN PELAJARAN 2023-2024 - Ahmad Kholilluloh; Topik, Patriana (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research aims to describe and analyze the use of the reading corner program in increasing interest in reading and the obstacles to its use at SDN 14 Trans Sabung. This research uses a qualitative approach and the type of research used is descriptive. The data collection techniques used were observation, interviews and documentation. Then the data analysis techniques used in this research are data reduction, data display/data presentation and drawing conclusions. Techniques for checking the validity of research data use: triangulation and member check. The results of this research show that: (1) Using reading corners to increase reading interest in class III students at SDN 14 Trans Sabung, namely (a) Creating reading corners in each class. (b) Organize and manage the class reading corner by the homeroom teacher and all students in the class. (c) The homeroom teacher always updates the collection of reading books in the reading corner once a month to ensure that students do not get bored with the existing reading books. (d) There is a collection list and a list of reading recaps for the class reading corner. (e) Utilizing the reading corner during class hours, namely with subjects that require students to read simply by taking a reading book from the reading corner. (f) There are activities for students to read independently using the class reading corner by taking advantage of school break time. (2) The obstacles experienced by teachers in using the reading corner to increase interest in reading for class III students at SDN 14 Trans Sabung are: (a) Lack of budget for the creation of a reading corner. (b) Lack of special time for reading by students in the class reading corner. (c) Lack of parental contribution in creating a reading corner. (d) The books available in the reading corner are still incomplete. (e) The teacher's role is not optimal in facilitating the reading corner. (f) Lack of student enthusiasm in reading. (3) the results of using the reading corner in increasing interest in reading for class III students at SDN 14 Tran Sabung, namely: (1) increasing the frequency of students' reading, (2) increasing students' reading skills, (3) increasing the school's quality scores in the field of literacy